Practical and Pedagogical Aspects of Learning Through Participation: the LTP Assessment Design Framework - Mackaway, Jacqueline; Winchester-Seeto, Theresa; Coulson, Debra; Harvey, Marina (Journal of University Teaching and Learning Practice, 2011)
Assessment of student learning in experience-based education is recognised as being a complex but important task. Practitioners are faced with a myriad of practical and pedagogical issues that influence what and how they assess, and can severely impact the effectiveness of assessment strategies. This paper presents a synthesised overview of the literature about assessment of student learning that is usually discussed in dispersed arenas and under different headings, such as work-integrated learning, cooperative education, practicum, project-based learning and service-learning etc. The term Learning through Participation (LTP) is introduced to cover all of these areas, but especially those where students undertake experiences and placements that incorporate community engagement and which are based within the curriculum. The literature in this area highlights a number of issues that add layers to the complexity of assessment of LTP. The synthesis presented herein discusses questions of validity, objective verification of learning, the roles and expectations of various stakeholders in the process of assessment, and the role and purpose of reflection in learning and assessment. To assist practitioners a LTP Assessment Design Framework has been created, which guides academics though a consideration and analysis of the practical and pedagogical context of LTP and some of the most important issues. The framework consists of two parts. The first part involves the development of a Placement Profile, to better understand the operational conditions for which the assessment package must be designed, and the second part is a set of Guiding Questions about assessment and feedback.